73.2k views
0 votes
In step 3, Ben made an error adding positive and negative numbers.

In step 4, Ben did not divide correctly


In step 1, Ben did not distribute the 2 correctly


In step 2, Ben did not maintain the equality of the equation

In step 3, Ben made an error adding positive and negative numbers. In step 4, Ben-example-1

1 Answer

3 votes

Answer:

In step 2, Ben did not maintain the equality

of the equation

Explanation:

2(-3x + 1) = 9x - 8 use the distributive property a(b + c) = ab + ac

2(-3x) + (2)(1) = 9x - 8

-6x + 2 = 9x - 8 subtract 2 and 9x from both sides

-6x - 9x = -8 - 2

Answer: In step 2, Ben did not maintain the equality of the equation.

combine like terms

-15x = -10 divide both sides by (-15)

x = 10/15

x = 2/3

User Darwayne
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.